1989
DOI: 10.1128/jcm.27.6.1230-1233.1989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six media for the growth of Trichomonas vaginalis from vaginal secretions

Abstract: Many media have been formulated for the growth of Trichomonas vaginalis, but the relative sensitivities of these media have not been determined. We evaluated the ability of six media, including all five media commercially available in the United States, to grow Trichomonas vaginalis from vaginal secretions. In a first experiment, we evaluated the ability of five media to grow T. vaginalis from vaginal secretions of 375 women and determined the optimal days on which to read culture tubes, by inoculating aliquot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 9 publications
2
22
0
3
Order By: Relevance
“…23 The type of formulations to be used for cultivating T. vaginalis should also be taken into account. Schmid et al 5 determined that Diamond TYM medium proved to be superior to other media used for T. vaginalis cultivation. In this study, Diamond TYM medium was used for maintaining T. vaginalis isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The type of formulations to be used for cultivating T. vaginalis should also be taken into account. Schmid et al 5 determined that Diamond TYM medium proved to be superior to other media used for T. vaginalis cultivation. In this study, Diamond TYM medium was used for maintaining T. vaginalis isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The culture method offers more sensitivity but with a longer turnaround period of at least 7 days to obtain the final result. 5 Current rapid methods in the specific detection of T. vaginalis are serologic-based but may exhibit cross-reaction with other trichomonads. 6 We have recently reported the prevalence of T. vaginalis in vaginal swabs from sex workers in Angeles City, Philippines using PCR utilizing T. vaginalis-specific primers.…”
Section: Introductionmentioning
confidence: 99%
“…Culture is considered the most reliable method of diagnosis but requires a special medium and frequent microscopic observation for up to 7 days (12,14,20). The sensitivity of culture is less than 90%, allowing for false negatives due to lack of detection of nonviable or small numbers of parasites (3,10,25). Cytology preparations, such as Papanicolaou's stain test (Pap smear) (10,19,29), also lack both sensitivity and specificity.…”
mentioning
confidence: 99%
“…When two media were used concurrently for diagnosis by of T. vaginalis is the most sensitive the culture method, Krieger et al (11) reported a 7% trichomoniasis (2,8,10,11,13,15,17), increase in sensitivity compared with that when a single nce has prevented it from being widely culture was used. Similarly, when the results obtained by linical laboratory procedure.…”
Section: Resultsmentioning
confidence: 99%
“…In the diagnosis of Trichomonas vaginalis, culture of the organism has been shown to be more sensitive than immediate examination of glass slide wet mount preparations (2,8,10,11,13,15,17). Several investigators reported superior results (2, 10, 11, 15) when both methods were used to make a diagnosis.…”
mentioning
confidence: 99%